THE INTERFERENCE OF CULTURAL HERITAGE IN THE SEXUAL EDUCATION OF SCHOOL AGENTS: A STUDY OF ONE CHILD INSTITUTION OF THE COUNTRYSIDE OF SAO PAULO - Celli de Oliveira, Maria Fernanda [UNESP]; Muzzeti, Luci Regina [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2021)
Sex education is still a taboo subject and working on it is essential for a natural and integral formation of each and every individual from an early age. Based on this vision, the present work aims to analyze and unveil, based on the analysis of three school agents of an Institution of Early Childhood Education, how the cultural heritage cultivated within the family can come to interfere in the work of issues related to sexuality inside and outside the school environment. To carry out this study we started from the concepts elaborated by Pierre Bourdieu, and to analyze the data we used the praxeological method, also elaborated by the French sociologist and his team. The study proposed here was intended to raise some discussions about the interference of family inheritance on sexuality.
Keywords: School agents; Child education; Sex education; Cultural heritage